Utilization of complementary and alternative medicine by patients undergoing maintenance hemodialysis for chronic kidney disease in Taiwan: a descriptive investigation - Ming-Yen Tsai; Chieh-Ying Chin; Wen-Chin Lee; Yu-Chuen Huang; Yu-Chen Cheng (BMC, 2024)
Abstract Background Despite the paucity of scientific evidence, complementary and alternative medicine (CAM) is widely used for the prevention and treatment of chronic illness, holistic care, and counteracting the adverse effects of conventional therapies. This study aims to determine the prevalence of CAM use and its associated factors among patients undergoing hemodialysis (HD) in Taiwan. Methods This quantitative study was conducted from August 2022 to July 2024 in the HD unit at Kaohsiung Chang Gung Memorial Hospital in Taiwan. Face-to-face questionnaire-based interviews were held with 154 of 163 eligible patients (response rate, 94.5%) at the bedside during HD. The completed questionnaires were entered into a secure computer database. Data was performed by descriptive analysis, Chi-square, and Fisher tests. Results More than half of the patients were CAM users (n = 86; 56%), and women was associated with significantly more usage of CAM. Fifty-six CAM users took Chinese herbal medicine (CHM), 52.3% (n = 45) used dietary supplements, and 19.8% (n = 17) used acupuncture. The benefit in the effectiveness of CAM was the main reason for use, the need of CAM to improve the well-being and HD-related complication was high. 32.7% of patients had used CAM based on recommendation from their family and friends. More than one-third (33.7%) of patients did not disclose their use of CAM to their doctors, most of them think it is unnecessary. Conclusions The use of CAM by patients with maintenance HD was relatively frequent. Of these, most used CHM, of which are shown to the trend into routine HD care is inevitable by high coverage and utilization in Taiwanese national health insurance system. These findings indicate that it is important for health care providers working in dialysis to assess CAM use.